Developing instructional materials on mathematics logical thinking through the Indonesian realistic mathematics education approach - Rahmi Purwitaningrum; Rully Charitas Indra Prahmana (International Journal of Education and Learning, 2021)
Instructional materials are one of the essential parts to support the learning process becomes more exciting and meaningful. However, teachers do not yet give more attention to these parts, so that the learning process becomes uninteresting and boring. Therefore, this research aims to produce the instructional materials for the logical thinking of mathematics ability based on Indonesian Realistic Mathematics Education for junior high school students for Grade 8, which is valid and practical. This research used a design research method with the type of development study conducted in two stages, namely preliminary design and formative evaluation, including self-evaluation, prototyping (expert reviews, one-to-one, and small groups) field tests the research conducted at junior high school. For research subjects, students of class VIII B of junior high school are 29 students. The techniques of data collection used are documentation, walkthrough, interviews, and test. The research data are quantitatively and qualitatively analyzed. The results of data analysis known that this research produces the logical thinking of mathematics for instructional materials based on Indonesian Realistic Mathematics Education on the content of linear equations of two variables that are valid, practical, and have potential effects. In this case, mathematics instructional materials in students' worksheets based on Indonesian Realistic Mathematics Education have been content valid, constructive, and language from expert validation at the expert review stage. In contrast, the mathematics student worksheets based on Indonesian Realistic Mathematics Education have been practically obtained from revisions results of one-to-one and small group. Furthermore, the prototype of instructional materials in the form of student worksheets has potential effects to improve the logical thinking of mathematics ability for students.